An MRTF-A–Sp1–PDE5 Axis Mediates Angiotensin-II-Induced Cardiomyocyte Hypertrophy - Wu, Teng; Wang, Huidi; Xin, Xiaojun; Xin, Xiaojun; Zhang, Tianyi; Hou, Yannan; Fang, Mingming; Lu, Xiang; Xu, Yong (Frontiers in Cell and Developmental Biology, 2020)
Cardiac hypertrophy is a critical intermediate step in the pathogenesis of heart failure. A myriad of signaling networks converge on cardiomyocytes to elicit hypertrophic growth in response to various injurious stimuli. In the present study we investigated the cardiomyocyte-specific role of myocardin-related transcription factor A (MRTF-A) in angiotensin II (Ang II) induced cardiac hypertrophy and the underlying mechanism. We report that conditional MRTF-A deletion in cardiomyocytes attenuated Ang II induced cardiac hypertrophy in mice. Similarly, MRTF-A knockdown or inhibition suppressed Ang II induced pro-hypertrophic response in cultured cardiomyocytes. Of note, Ang II treatment up-regulated expression of phosphodiesterase 5 (PDE5), a known mediator of cardiac hypertrophy and heart failure, in cardiomyocytes, which was blocked by MRTF-A depletion or inhibition. Mechanistically, MRTF-A activated expression of specificity protein 1 (Sp1), which in turn bound to the PDE5 promoter and up-regulated PDE5 transcription to promote hypertrophy of cardiomyocytes in response to Ang II stimulation. Therefore, our data unveil a novel MRTF-A-Sp1-PDE5 axis that mediates Ang II-induced hypertrophic response in cardiomyocytes. Targeting this newly identified MRTF-A-Sp1-PDE5 axis may yield novel interventional solutions against heart failure.